Impact of BCG vaccination and metabolic risk factors on the severity of SARS-Cov-2 infection: a cross-sectional study from a tertiary care centre in northern India - N. N. Begam; G. Gupta; S. Chatterji; A. Narayan; S. Pandey; S. Tomar; S. Sinha (Sri Lankan Journal of Infectious Diseases, 2022)
Background and aims: We present a study on the earliest cohort of patients infected with the SARS-CoV-2 virus who were admitted to the All India Institute of Medical Sciences (AIIMS), New Delhi. The primary objective of the study was to find the difference in the rate of intensive care unit (ICU) admission with coronavirus disease 2019 (COVID-19) in patients based on BCG vaccination status. The secondary objective was to assess risk factors for ICU admission and clinical course of patients with COVID-19.   Methods: A cross-sectional observational study was done between 1 May 2020 and 30 July 2020 in AIIMS, New Delhi. Patients aged more than 14 years attending or admitted to the COVID-19 facility with suspected or confirmed SARS-CoV-2 infection were screened and 205 patients with confirmed COVID-19 were included in the study. Patients were managed as per standard protocol. The difference in ICU admission rate with COVID-19 in patients with and without metabolic risk factors was analysed.    Results: The study shows higher ICU admission in the age group ≥45-75years (n=16; 68.5%) compared to the age group 15-44 (n=10; 38.5%) which was statistically significant (p=0.01). In multivariate analysis, the age group ≥45-75 years [AOR=3.76, 95% CI (1.10,12.82), p=0.03] and diabetes mellitus [AOR=5.20, 95% CI (1.08,25.16), p=0.04] were significantly associated with higher ICU admission. Of the 26 patients admitted to ICU, 4 (15.3%) were vaccinated in contrast to 22 (84.6%) who were unvaccinated (p<0.001).   Conclusion: Diabetes was strongly associated with ICU admission and appears to be a risk factor for severity in patients with COVID-19. BCG vaccination status is positively correlated with fewer ICU admission rates in patients with COVID-19.